Implementasi Model Peer Teaching Untuk Meningkatkan Partisipasi Aktif Siswa Pada Pembelajaran PJOK - Septianti, Lastri; Sonjaya, Azhar Ramadhana; Hermawan, Irwan; Arifin, Z. (Universitas Hamzanwadi, 2025)
This study aims to analyze the effectiveness of the implementation of the peer teaching model in increasing students' active participation in learning (PJOK). This study used a quasi-experimental method with a pretest and posttest control group design. The population of this study were 8th grade students at MTs Al-Musaddadiyah Garut consisting of 60 students. The research sample was taken by random sampling, with two groups consisting of an experimental group taught with a peer teaching model and a control group taught with conventional methods. The data collection instrument used was a student active participation questionnaire which included four aspects of emotional involvement, cognitive involvement, behavioral involvement, and social involvement. The data analysis technique used statistical tests to compare pretest and posttest results between groups. The results showed a significant difference in the active participation of students taught with the peer teaching model compared to students taught with conventional methods. Students' active participation increased by 25.25%, The average difference between the two groups was 34.10 with a 95% confidence interval between 31.07 and 37.13. The application of peer teaching model is proven to be effective in increasing students' active participation in learning PJOK, especially in terms of physical involvement, social interaction, and material understanding.